Kritik Terhadap Indeks Implementasi Zakat Core Principles - AS Rakhmat; Busaid (DPPM Universitas Pelita Bangsa, 2023)
The Zakat Core Principle (ZCP) is intended to support the improvement of the quality of the zakat system and the effectiveness of the Zakat Management Organization. ZCP is a zakat management principle consisting of 18 principles which are grouped into 6 (six) main dimensions of zakat management. The six dimensions are legal basis, zakat supervision, zakat governance, intermediation function, risk management, and sharia compliance. ZCP aimed to improve the quality of zakat management so that it is more effective in mobilizing public social funds for improving people's welfare. This research uses descriptive-critical analysis method. This analysis begins by describing the ZCP Implementation Index, then analyzing the things that can be criticized from the ZCP Implementation Index. The authors did not criticize the 18 principles, so for further researchers, it is hoped to continue this critical study of ZCP. It is required also this critical Study will assist BAZNAS in developing the ZCP concept.